ESTV 1ª Edição, é a Gente Com Você: Análise Sociolinguística da Variação Pronominal de Primeira Pessoa do Plural em Jornal Televisionado - Dias, Kaio Rangel da Silva (2021)
In this assignment, the goals and main ideas are to describe and analyze the phenomenon of the pronominal alternation nós and a gente (we / us) in the speech of the participants in the ESTV 1st edition newscast, shown daily, around 11:45 A.M to 1:00 P.M, in the metropolitan region of Grande Vitória - ES, for TV Gazeta, a broadcaster affiliated with Rede Globo. In this regard, Variationist Sociolinguistics is used as a theoretical perspective, based on the actual use of language by speakers, based on the idea that variation is a constituent part of the linguistic system, being inherent to it and, therefore, possible to find a description and analyze. The data used for this study was recorded from the newscast itself and it consists of 47 audio videos recordings (27 full episodes / 20 interview situations in the studio), coded for further quantification using the GoldvarbX software (SANKOFF; TAGLAMONTE; SMITH 2005) and analysis of quali-quantitative nature. To quantify the data, the GoldvarbX program (SANKOFF; TAGLAMONTE; SMITH 2005) was used, and the factors analyzed were the speaker's social role, the speaker's gender, the discursive sequence, the discursive topic, the syntactic function, the interlocutor, the verbal tense and the phonic salience - in the case of a subject - from all contexts with the occurrence of the pronouns in question. The results show, in line with previous studies related to the speech of Vitória - ES, in the context of the television news studied, 68.0% of frequency of use of the innovative form as opposed to 32.0% of use of the canonical form. From the 3986 data analyzed, it is highlighted that i) the announcers who most favor the use of us are the anchor journalists, responsible for the presentation of the newscast, and those who are most disadvantaged are the interviewees, while the street reporters, do not seem to favor or disadvantage the occurrence of people; ii) women are the ones that stand out the most in relation to the use of the innovative pronominal form; iii) the syntactic function with the highest number of occurrences is the one about "subject", and that favors us most is that of indirect object; iv) the cases of past imperfect (used to) and ambiguous present are those that most favor the use of the innovative form, whereas the less ambiguous present behaves in a neutral way and the less ambiguous past tense cases present less favorable behavior to "a gente" (we); v) the internal discursive sequences are the ones that most favor the use of the canonical form, as opposed to the external sequences, in which people predominate; and vi) political interlocutors and public people are those who favor the use of people in the context studied.